Optimization of Tofu Raw Material Inventory Using the Dynamic Lot Sizing Method - Ningsi, Ria Sagita; Cipta, Hendra (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
The purpose of this study was to determine the lot size of tofu raw materials orders, the total cost of factory inventory before and after implementing inventory control using the Wagner-Within Algorithm technique on the Dynamic Lot Sizing method. With demand forecasting on the POM QM aplication consisting of Moving Average, Weighted Moving Average, and Exponential Smoothing. Based on the result obtained, the total lot size of tofu raw material orders without implementing inventory control of 15.800 kilos per year. The total cost is Rp. 189.656.040 and is more optimal when compared to the factory system, which is Rp. 208.256.040 so that the factory can save costs of Rp. 18.600.000.